2018
DOI: 10.1017/dmp.2018.20
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nepal Earthquake on Patients Presenting for Emergency Care at Patan Hospital

Abstract: Understanding emergency department utilization after the earthquake has the potential to give further insight into improving disaster preparedness plans for post-disaster health needs. (Disaster Med Public Health Preparedness. 2018;page 1 of 6).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
(38 reference statements)
0
6
1
Order By: Relevance
“…Respondents with psychiatric illnesses did not show an increase in alcohol intake as compared to healthy control groups. This observation is different from the previous study, which reported the increase in alcohol intoxication and abuse after natural disasters (e.g., earthquake) (Tembe et al, 2019). As the government implemented outing restriction during the COVID-19 epidemic for all citizens, people with and without psychiatric illnesses did not have frequent access to purchase alcohol from local supermarkets.…”
Section: Discussioncontrasting
confidence: 84%
“…Respondents with psychiatric illnesses did not show an increase in alcohol intake as compared to healthy control groups. This observation is different from the previous study, which reported the increase in alcohol intoxication and abuse after natural disasters (e.g., earthquake) (Tembe et al, 2019). As the government implemented outing restriction during the COVID-19 epidemic for all citizens, people with and without psychiatric illnesses did not have frequent access to purchase alcohol from local supermarkets.…”
Section: Discussioncontrasting
confidence: 84%
“…One explanation is the fact that respiratory conditions sustained would not require hospitalization, and would rather be reflected in outpatient care. Indeed, a study in a hospital near Kathmandu found an increase in emergency department visits due to respiratory diseases [ 37 ]. Such an explanation is not plausible for pregnancy-related admissions, and it may indicate that pregnant women are not receiving skilled care and deliveries are not conducted in health facilities.…”
Section: Resultsmentioning
confidence: 99%
“…As such, most respiratory consequences of the 2015 earthquake would be reflected in outpatient care. A study in Patan Hospital, in the vicinity of Kathmandu, showed that there were significantly more emergency visits due to cardiovascular, psychiatric, respiratory, and hematologic conditions in the four months after the earthquake, compared to the same period one year before 19 .…”
Section: Discussionmentioning
confidence: 99%